2013
DOI: 10.1680/feng.12.00023
|View full text |Cite
|
Sign up to set email alerts
|

Snow load damage to buildings: physical and economic impacts

Abstract: This study examines the physical and economic impacts of snow-related building failures occurring in the USA between autumn 2008 and spring 2011. The study employed a web-based survey distributed to owners and operators of 332 buildings. These buildings were identified in newspaper archives or online news sources as having been damaged by snow loads. This paper describes the 40 responses received. Damage to these buildings ranged from minor to complete collapse; survey responses showed that the roof structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These snow-related failures can be catastrophic to local economies, like the recent $100 million in losses incurred by Idaho/Oregon's onion industry (Ellis 2017). One study of 40 snow-induced building failures reported an average cost of $166 per square meter and 122 days of business interruption for repairs (Strobel and Liel 2013). Snow-related damages can extend beyond building repairs, as a study of 1,100 domestic and international snow-induced building failures reported more than 300 fatalities (Geis et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These snow-related failures can be catastrophic to local economies, like the recent $100 million in losses incurred by Idaho/Oregon's onion industry (Ellis 2017). One study of 40 snow-induced building failures reported an average cost of $166 per square meter and 122 days of business interruption for repairs (Strobel and Liel 2013). Snow-related damages can extend beyond building repairs, as a study of 1,100 domestic and international snow-induced building failures reported more than 300 fatalities (Geis et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The author presents a number of case studies, and, usefully, groups them by theme, such as the role of workmanship, unexpected events and concrete cracking. By selecting such groupings rather than simply presenting a range of failures, he provides further insight into the causes of these issues and stresses the importance of the straightforward, but often neglected, measures that avert failure, such as the role of site supervision.The approach of examining failure from a broad perspective is continued by Strobel and Liel (2013), who in our second paper examine snow load failures to buildings in the USA from both a physical and economic perspective. Characteristics examined range from the types of buildings affected by snow loading, the types of physical damage and the sequences of events following failures, including downtime and insurance cover.…”
mentioning
confidence: 99%
“…The approach of examining failure from a broad perspective is continued by Strobel and Liel (2013), who in our second paper examine snow load failures to buildings in the USA from both a physical and economic perspective. Characteristics examined range from the types of buildings affected by snow loading, the types of physical damage and the sequences of events following failures, including downtime and insurance cover.…”
mentioning
confidence: 99%